Charge Transfer Complexes based on Various Amines as Dual Thermal and Photochemical Polymerization Initiators: A Powerful Tool for the Access to Composites. Issue 6 (20th January 2020) - Wang, Dengxia; Arar, Ahmad; Garra, Patxi; Graff, Bernadette; Lalevée, Jacques
ABSTRACT: Exploiting highly efficient, environmentally friendly, and economic CTCs (Charger Transfer Complexes) as photo/thermal dual initiators is a huge pursuit of materials practitioners and innovators. To investigate and find out series amines as donors in CTCs, RT‐FTIR (Real‐Time Fourier Transform Infrared Spectroscopy) was employed to examine the photo initiating efficiency of CTCs based on amines donors and DSC (Differential Scanning Calorimeter) was used to test their thermal initiating ability. The formation of CTCs was investigated and confirmed by molecular orbital (MO) calculations and UV–Vis experimental study. Structure/reactivity/efficiency relationships will be proposed on the base of more than 10 new amine donors. At last, composites based on glass fibers and carbon fibers were fabricated by photo curing and/or photo/thermal dual curing method, which showed excellent mechanical performance in DMA (Dynamic Mechanical Analysis) characterization. This work paves the path toward flexible photo/thermal dual initiators able to react on demand thanks to orthogonal stimuli (light or heat with the same initiating system). It will naturally find use in time and spatially resolved composites manufacturing (were classical simple photoinitiating or thermal systems are inefficient). © 2020 Wiley Periodicals, Inc. J. Polym. Sci. 2020, 58, 811–823 Abstract : CTCs based on various amines as dual photo/thermal initiators were investigated. The new CTCs exhibited good spatial control ability in 3D printing process and excellent initiating ability in composites fabrication. Dual photo/thermal versatile initiating systems fill technological limitations shown by single photo or thermal initiators.